Climate shocks constrain human fertility in Indonesia. (May 2019) - Sellers, Samuel; Gray, Clark
Highlights: Climate change can affect human fertility, family planning use, and births. We find recent delays in monsoon rains are linked with lower family planning use. Women on farms exposed to high temperatures are less likely to give birth. Pathways linking climate change, livelihoods and fertility behaviors are unclear. Abstract: Climate change is likely to induce a large range of household- and individual-level responses, including changes in human fertility behaviors and outcomes. These responses may have important implications for human and economic development and women's empowerment. Drawing on the literature linking climate conditions to rice cultivation in Indonesia, we use longitudinal household survey and high-resolution climate data to explore changes in childbearing intentions, family planning use, and births following community-level climate shocks from 1993 to 2015. We find that fertility intentions increase and family planning use declines in response to delays in monsoon onset occurring within the previous year, particularly for wealthier populations. However, women on farms are significantly more likely to use family planning and less likely to give birth following abnormally high temperatures during the previous five years. We also measure parallel shifts in household well-being as measured by rice, food, and non-food consumption expenditures. Our findings advance the environmental fertility literature by showing that longer duration environmental shocks can have impacts on fertility behaviors and outcomes. Collectively, our results illustrate human fertility responses to climate change in a country vulnerable to its effects, and demonstrate that in some cases, climate shocks can constrain human fertility.